2020
DOI: 10.1016/j.chempr.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Induced Selective Separation of Ortho-substituted Benzene Isomers Enabled by Cucurbit[7]uril Host Macrocycles

Abstract: The separation of benzene derivatives is energy intensive and laborious as a result of the overlapping physicochemical properties of these isomers. Here, we report on the separation of ortho-disubstituted benzene isomers using cucurbit[7]uril (CB7) aqueous solution with more than 92% selectivity. Thermodynamic and kinetic analysis proves that the ortho-isomer has stronger binding ability and slower decomplexation rate constant than the para-and metaisomers when hosted by CB7. Optimized host-guest models indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…The separation of xylene isomers is challenging because they have similar molecular structures and physical properties. Recently, molecular materials such as cucurbit [7]uril 38 and the polymorphic azobenzene cage 39 have been studied as adsorbents for the separation of xylene isomers. The largest included sphere along the free sphere path (D if ) calculated by Zeo++ 31,40 in activated 1-rac is 4.26 Å, which is close to the molecular size of para-xylene (pX) (4.2 Â 6.8 Å) (Table S1, ESI †).…”
mentioning
confidence: 99%
“…The separation of xylene isomers is challenging because they have similar molecular structures and physical properties. Recently, molecular materials such as cucurbit [7]uril 38 and the polymorphic azobenzene cage 39 have been studied as adsorbents for the separation of xylene isomers. The largest included sphere along the free sphere path (D if ) calculated by Zeo++ 31,40 in activated 1-rac is 4.26 Å, which is close to the molecular size of para-xylene (pX) (4.2 Â 6.8 Å) (Table S1, ESI †).…”
mentioning
confidence: 99%
“…These macromolecules show outstanding selectivity in the separation of compounds with similar physical properties, like boiling points or chromatographic behavior, such as xylenes, [2] chloropyridines, [3] and monochlorotoluenes [4] . Unlike the structurally related cucurbiturils, for which a comparable selectivity is reported, [5] nonporous adaptive crystals feature a certain degree of structural flexibility to adjust their cavity shape according to the guest molecule. Oxatubarenes, the most recently developed structural analogs, even undergo conformational conversions by flipping structural units to vary their cavity size [6] …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] These materials are amenable to selective host-guest recognition in liquid-based separation methodologies (e.g.l iquid-liquid extraction), which are known in industry for requiring relatively little energy. [21][22][23] Our group has recently shown that nanoscale cuboctahedral Rhodium-based Metal-Organic Polyhedra (Rh-MOPs), aclass of permanently porous metal-organic cages assembled from 24 (functionalised) 1,3-benzenedicarboxylate linkers and 12 dirhodium paddlewheels, [24] can also be harnessed for molecular separation, albeit through an alternative mechanism to host-guest recognition. Unlike other coordination cages,R h-MOPs present twelve Rh II paddlewheels,e ach of which has an exohedral open metal site that can be used to bind molecules with coordinating groups (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These materials are amenable to selective host‐guest recognition in liquid‐based separation methodologies (e.g. liquid‐liquid extraction), which are known in industry for requiring relatively little energy [21–23] …”
Section: Introductionmentioning
confidence: 99%